+0  
 
0
365
2
avatar

sqrt(x-2)+sqrt(x+1)= 27 sqrt(x+1)-sqrt(x-2)=?

Guest Mar 17, 2017
 #1
avatar
0

Solve for x:
sqrt(x - 2) + sqrt(x + 1) = 27 sqrt(x + 1) - sqrt(x - 2)

(sqrt(x - 2) + sqrt(x + 1))^2 = -1 + 2 x + 2 sqrt(x - 2) sqrt(x + 1) = -1 + 2 x + 2 sqrt((x - 2) (x + 1)) = (27 sqrt(x + 1) - sqrt(x - 2))^2:
-1 + 2 x + 2 sqrt((x - 2) (x + 1)) = (27 sqrt(x + 1) - sqrt(x - 2))^2

(27 sqrt(x + 1) - sqrt(x - 2))^2 = 727 + 730 x - 54 sqrt(x - 2) sqrt(x + 1):
-1 + 2 x + 2 sqrt((x - 2) (x + 1)) = 727 + 730 x - 54 sqrt(x - 2) sqrt(x + 1)

Subtract 2 x - 1 from both sides:
2 sqrt((x - 2) (x + 1)) = 728 + 728 x - 54 sqrt(x - 2) sqrt(x + 1)

Raise both sides to the power of two:
4 (x - 2) (x + 1) = (728 + 728 x - 54 sqrt(x - 2) sqrt(x + 1))^2

Combine sqrt(x - 2) and sqrt(x + 1) under the same square root:
4 (x - 2) (x + 1) = (728 + 728 x - 54 sqrt((x - 2) (x + 1)))^2

Expand out terms of the left hand side:
4 x^2 - 4 x - 8 = (728 + 728 x - 54 sqrt((x - 2) (x + 1)))^2

(728 + 728 x - 54 sqrt((x - 2) (x + 1)))^2 = 524152 + 1057052 x + 532900 x^2 + (-78624 - 78624 x) sqrt((x - 2) (x + 1)):
4 x^2 - 4 x - 8 = 524152 + 1057052 x + 532900 x^2 + sqrt((x - 2) (x + 1)) (-78624 - 78624 x)

Subtract 524152 + 1057052 x + 532900 x^2 + (-78624 - 78624 x) sqrt((x - 2) (x + 1)) from both sides:
-524160 - 1057056 x - 532896 x^2 - sqrt((x - 2) (x + 1)) (-78624 - 78624 x) = 0

Add 532896 x^2 + 1057056 x + 524160 to both sides:
sqrt((x - 2) (x + 1)) (78624 x + 78624) = 532896 x^2 + 1057056 x + 524160

Raise both sides to the power of two:
(x - 2) (x + 1) (78624 x + 78624)^2 = (532896 x^2 + 1057056 x + 524160)^2

Expand out terms of the left hand side:
6181733376 x^4 + 6181733376 x^3 - 18545200128 x^2 - 30908666880 x - 12363466752 = (532896 x^2 + 1057056 x + 524160)^2

Expand out terms of the right hand side:
6181733376 x^4 + 6181733376 x^3 - 18545200128 x^2 - 30908666880 x - 12363466752 = 283978146816 x^4 + 1126601828352 x^3 + 1676012921856 x^2 + 1108132945920 x + 274743705600

Subtract 283978146816 x^4 + 1126601828352 x^3 + 1676012921856 x^2 + 1108132945920 x + 274743705600 from both sides:
-277796413440 x^4 - 1120420094976 x^3 - 1694558121984 x^2 - 1139041612800 x - 287107172352 = 0

The left hand side factors into a product with four terms:
-76317696 (x + 1)^2 (56 x + 57) (65 x + 66) = 0

Divide both sides by -76317696:
(x + 1)^2 (56 x + 57) (65 x + 66) = 0

Split into three equations:
(x + 1)^2 = 0 or 56 x + 57 = 0 or 65 x + 66 = 0

Take the square root of both sides:
x + 1 = 0 or 56 x + 57 = 0 or 65 x + 66 = 0

Subtract 1 from both sides:
x = -1 or 56 x + 57 = 0 or 65 x + 66 = 0

Subtract 57 from both sides:
x = -1 or 56 x = -57 or 65 x + 66 = 0

Divide both sides by 56:
x = -1 or x = -57/56 or 65 x + 66 = 0

Subtract 66 from both sides:
x = -1 or x = -57/56 or 65 x = -66

Divide both sides by 65:
x = -1 or x = -57/56 or x = -66/65

sqrt(x - 2) + sqrt(x + 1) ⇒ sqrt(-2 - 57/56) + sqrt(1 - 57/56) = i sqrt(7/2) ≈ 1.87083 i
27 sqrt(x + 1) - sqrt(x - 2) ⇒ 27 sqrt(1 - 57/56) - sqrt(-2 - 57/56) = i sqrt(7/2) ≈ 1.87083 i:
So this solution is correct

sqrt(x - 2) + sqrt(x + 1) ⇒ sqrt(-2 - 66/65) + sqrt(1 - 66/65) = 3 i sqrt(5/13) ≈ 1.86052 i
27 sqrt(x + 1) - sqrt(x - 2) ⇒ 27 sqrt(1 - 66/65) - sqrt(-2 - 66/65) = i sqrt(13/5) ≈ 1.61245 i:
So this solution is incorrect

sqrt(x - 2) + sqrt(x + 1) ⇒ sqrt(-2 - 1) + sqrt(1 - 1) = i sqrt(3) ≈ 1.73205 i
27 sqrt(x + 1) - sqrt(x - 2) ⇒ 27 sqrt(1 - 1) - sqrt(-2 - 1) = -i sqrt(3) ≈ -1.73205 i:
So this solution is incorrect

The solution is:
Answer: |x = -57/56 - (assuming a complex-valued square root)

Guest Mar 17, 2017
 #2
avatar+26816 
0

Probably better to add sqrt(x-2) to both sides and subtract sqrt(x+1) from both sides first, before thinking about squaring!

Alan  Mar 17, 2017

6 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.